Hybrid fuzzy-fuzzy controller for PWM-driven induction motor drive - Magzoub, M.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper represents a method for the designing and developing of a hybrid fuzzy-fuzzy control (HFFC) scheme to gain control over the speed of an induction motor (IM). The fuzzy frequency control and fuzzy current amplitude control are studied in a closed-loop current amplitude input model for an induction motor. A combination of both controllers forms the hybrid controller. The principle of HFFC is to control the rotor speed during acceleration-deceleration stage using fuzzy frequency controller and during steady-state stage using fuzzy stator current magnitude controller to overcome the drawback of field oriented control (FOC) method. The two features (frequency and current) of FOC are employed to design a scalar controller. The software, MATLAB/Simulink is used for the simulation to determine the performance of the controller. A series of tests has been conducted to study the performance of the controller and the results shown that the controller is more reliable and insensitivity to the parameters of the motor changes as compared to the classical indirect field-oriented control (IFOC). Â© 2014 IEEE.